Answer:
4). 47 - 29i
Step-by-step explanation:
(5+√-36)*(1-√-49)=5*1 -5√-49+1*√-36 -√-36√-49 = 5-5*7i +6i-6i*7i=
=5-35i+6i-42(-1)=5+42-41i= 47 - 29i
9514 1404 393
Answer:
Step-by-step explanation:
The answer statement tells you the transformation is a rotation. The original is in the 2nd quadrant, and the image is in the 1st quadrant, representing a clockwise rotation. AB points east, while A'B' points south, a rotation of 90° (clockwise). Each image point is the same distance from the origin as its preimage point. The origin is the center of rotation.
__
∆ABC is transformed by a <u> clockwise </u> rotation <u> 90 </u> degrees with a center at the <u> origin </u>.
90/2 = 45
45/1700 = 0.02647
0.02647 x 100 = 2.64
2.46%
For proof of 3 divisibility, abc is a divisible by 3 if the sum of abc (a + b + c) is a multiple of 3.
<h3>
Integers divisible by 3</h3>
The proof for divisibility of 3 implies that an integer is divisible by 3 if the sum of the digits is a multiple of 3.
<h3>Proof for the divisibility</h3>
111 = 1 + 1 + 1 = 3 (the sum is multiple of 3 = 3 x 1) (111/3 = 37)
222 = 2 + 2 + 2 = 6 (the sum is multiple of 3 = 3 x 2) (222/3 = 74)
213 = 2 + 1 + 3 = 6 ( (the sum is multiple of 3 = 3 x 2) (213/3 = 71)
27 = 2 + 7 = 9 (the sum is multiple of 3 = 3 x 3) (27/3 = 9)
Thus, abc is a divisible by 3 if the sum of abc (a + b + c) is a multiple of 3.
Learn more about divisibility here: brainly.com/question/9462805
#SPJ1